Large Hadron Collider momentum calibration and accuracy - E. Todesco; J. Wenninger (Physical Review Accelerators and Beams, 2017)
As a result of the excellent quality of the Large Hadron Collider (LHC) experimental detectors and the accurate calibration of the luminosity at the LHC, uncertainties on the LHC beam energy may contribute significantly to the measurement errors on certain observables unless the relative uncertainty is well below 1%. Direct measurements of the beam energy using the revolution frequency difference of proton and lead beams combined with the magnetic model errors are used to provide the energy uncertainty of the LHC beams. Above injection energy the relative uncertainty on the beam energy is determined to be ±0.1%. The energy values as reconstructed and distributed online to the LHC experiments do not require any correction above injection energy. At injection a correction of +0.31  GeV/c must be applied to the online energy values.